Associating factors in postmenopausal women with pelvic organ prolapse - Daniyal, Laraib (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
I have reviewed with deep interest the publication "the evaluation between vitamin D level and pelvic organ prolapse in postmenopausal women." As a medical student, I appreciate all authors on their dedicated work and would like to express my gratitude for their findings. This study investigated the association between vitamin D levels and pelvic organ prolapse in postmenopausal women.